Matrix habitat and species richness in tropical forest remnants - Gascon, Claude; Lovejoy, Thomas E.; Bierregaard, Richard O.; Malcolm, Jay R.; Stouffer, Philip C.; Vasconcelos, Heraldo L.; Laurance, William F.; Zimmerman, Barbara L.; Tocher, Mandy D.; Borges, Sérgio Henrique (Biological Conservation, 1999)
The abilities of species to use the matrix of modified habitats surrounding forest fragments may affect their vulnerability in fragmented landscapes. We used long-term (up to 19-year) studies of four animal groups in central Amazonia to test whether species' abundances in the matrix were correlated with their relative extinction proneness in forest fragments. The four groups, birds, frogs, small mammals, and ants, had varying overall responses to fragmentation: species richness of small mammals and frogs increased after fragment isolation, whereas that of birds and ants decreased. For all four groups, a high proportion of nominally primary-forest species were detected in matrix habitats, with 8-25% of species in each group found exclusively in the matrix. The three vertebrate groups (birds, small mammals, frogs) exhibited positive and significant correlations between matrix abundance and vulnerability to fragmentation, suggesting that species that avoid the matrix tend to decline or disappear in fragments, while those that tolerate or exploit the matrix often remain stable or increase. These results highlight the importance of the matrix in the dynamics and composition of vertebrate communities in tropical forest remnants, and have important implications for the management of fragmented landscapes.
Keywords: Fauna; Habitat Fragmentation; Habitat Mosaic; Habitat Use; Species Richness; Tropical Forest; South America